Do you know the diagnostic importance of susceptibility‐weighted imaging on MRI for patients with cerebral fat embolism? - Yuki Koshida; Mitsushige Nishimura; Kenji Kanazawa (Clinical Case Reports, 2023)
Key Clinical Message If you suspect cerebral fat embolism (CFE) of the diagnosis for the patients who present with impaired consciousness and hypoxia following a fracture, susceptibility‐weighted imaging should be included of head MRI imaging. Abstract We report a case of cerebral fat embolism (CFE) that could be identified only by susceptibility‐weighted imaging (SWI). Collection and analysis of previous case reports of CFE revealed utilization of SWI in less than one third of suspected cases, despite its known diagnostic ability for CFE.